2019
DOI: 10.3390/nu11051072
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 12 Weeks of Hypertrophy Resistance Exercise Training Combined with Collagen Peptide Supplementation on the Skeletal Muscle Proteome in Recreationally Active Men

Abstract: Evidence has shown that protein supplementation following resistance exercise training (RET) helps to further enhance muscle mass and strength. Studies have demonstrated that collagen peptides containing mostly non-essential amino acids increase fat-free mass (FFM) and strength in sarcopenic men. The aim of this study was to investigate whether collagen peptide supplementation in combination with RET influences the protein composition of skeletal muscle. Twenty-five young men (age: 24.2 ± 2.6 years, body mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(83 citation statements)
references
References 67 publications
(75 reference statements)
5
71
0
Order By: Relevance
“…In line with this, there is emerging evidence of benefits associated with the ingestion of collagen peptides in a range of collagen containing tissues, including increased collagen synthesis (22, 23), improved body composition (24, 25), reduced pain (2628) and the slowing of degenerative diseases such as osteoarthritis (29, 30). It has been suggested that hydrolysis of collagen protein prior to ingestion allows two and three amino acid peptides to pass across the mucosal barrier equating to a higher expression and therefore biosynthesis within the tissue matrix (31).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…In line with this, there is emerging evidence of benefits associated with the ingestion of collagen peptides in a range of collagen containing tissues, including increased collagen synthesis (22, 23), improved body composition (24, 25), reduced pain (2628) and the slowing of degenerative diseases such as osteoarthritis (29, 30). It has been suggested that hydrolysis of collagen protein prior to ingestion allows two and three amino acid peptides to pass across the mucosal barrier equating to a higher expression and therefore biosynthesis within the tissue matrix (31).…”
Section: Introductionmentioning
confidence: 85%
“…This was illustrated in a recent study whereby the consumption of hydrolysed collagen proteins resulted in a higher bioavailability of AAs compared to non-hydrolysed collagen protein and a placebo control (32). Furthermore, it has recently been shown that the consumption of collagen peptides resulted in a higher expression of collagen signaling proteins, compared to a placebo control (24).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, up to 80% of the contractile force is transmitted laterally to the extracellular matrix ( 15 ). Therefore, it seems evident that connective tissue in skeletal muscle must undergo extensive remodeling after acute exercise ( 16 , 17 ) as well as during prolonged exercise training ( 18 ) to allow the concomitant gains in both muscle mass and muscle strength. In support, exercise has been reported to increase intramuscular connective tissue protein synthesis rates ( 16 , 17 , 19 22 ).…”
mentioning
confidence: 99%
“…Moreover, in the western population, there is an apparent shift towards increased consumption of plant-derived protein (in lieu of animal), due to perceived health benefits (e.g., reduced cardiovascular mortality [22]) and environmental sustainability [6]. Reflecting this shift, while the majority of prior research investigations have focused upon characterising the effects of animal-derived proteins in relation to musculoskeletal metabolism and health, there has been a recent surge of studies investigating the influence of plant-derived (e.g., References [4,[23][24][25]), collagen-derived (e.g., References [26][27][28][29]) and blended (e.g., References [30][31][32]) protein sources.…”
Section: Dietary Protein Requirementsmentioning
confidence: 99%
“…Nevertheless, pre-clinical models have shown collagen-specific peptides to offset disease-induced muscle wasting [124], inhibit age-related muscle oxidative decline [125] and promote muscle hypertrophy via increased mTOR signalling [122], therein demonstrating the anabolic potential of supplemental collagen-derived proteins. This, coupled with the fact that dietary collagen has superb digestibility and becomes rapidly bioavailable following consumption in humans [28,126], suggests that there is potential for dietary collagen to mediate human skeletal muscle and bone remodelling. However, to date, the effects of collagen supplementation on muscle health across age, in the absence of allied exercise, has been sparsely studied.…”
Section: Skeletal Musclementioning
confidence: 99%